Methyltransferase-like 3-mediated RNA N6-methyladenosine contributes to immune dysregulation: diagnostic biomarker and therapeutic target - Zhang, Deshuang; Xu, Ting; Gao, Xiaoxue; Qu, Yi; Su, Xiaojuan (Frontiers in Immunology, 2025)
Methyltransferase-like 3 (METTL3) plays a crucial role in post-transcriptional gene regulation. Substantial evidence links METTL3 to various immune dysfunctions, such as the suppression of antiviral immunity during viral infections and the disruption of immune tolerance in conditions like autoimmune diseases, myeloid leukemia, skin cancers, and anticancer immunotherapy. However, a thorough review and analysis of this evidence is currently missing, which limits the understanding of METTL3’s mechanisms and significance in immune dysfunctions. This review aims to elucidate the roles and mechanisms of METTL3 in these immune issues, highlighting its connections and proposing new insights into its modulation of immune responses. Analysis results in this review suggest that METTL3 hampers antiviral immunity, worsens viral replication and infection, and disrupts immune tolerance; conversely, regulating METTL3 enhances antiviral immunity and facilitates viral clearance. Moreover, clinical data corroborates these findings, showing that METTL3 overexpression is associated with increased susceptibility to viral infections and autoimmune conditions. This review establishes a theoretical basis for considering METTL3 as a novel regulator, an important diagnostic biomarker, and a potential target for treating immune dysfunctions.